COLORS DISTRIBUTION IN POLYMER WASTES AND COLOR PREDICTION OF RECYCLED POLYMERS - Patachia, Silvia; Croitoru, Catalin; Baltes, Liana; Tierean, Mircea (GH ASACHI TECHNICAL UNIV IASI71 MANGERON BLVD, IASI 700050, ROMANIA, 2019)
In this paper, several image analysis techniques have been applied aiming to obtain useful information regarding the processing of municipal solid waste polymers. An automated color extraction method has been applied in order to quantize the color distribution in the polymer wastes aiming their resource and time-efficient separation according to their color. Also, by processing different density fractions from the polymer waste the color of the final material has been predicted, as well as the potential degradation of the material in the processing conditions used in the study. The image analysis techniques used in this paper could complement other polymer characterization techniques and could lead to an increase in the efficiency of waste recycling management by efficiently planning-ahead of the processing parameters and of the raw materials used (dyes, pigments).
Keywords: colour distribution; image analysis; polymer composite; polymer waste; separation